Experience-centric leadership development process: challenges and way forward for organisations in India. (2018) - Panda, Abinash
Various academic scholars from leadership development discipline have found that experience-centric approach, compared to formal education and training-based approach is more effective for grooming organisational leaders. The world of academe offers plenty of insights on experience-centric leadership development process. In spite of such rich insights, business organisations have stuck to formal training and education-based approach for grooming leaders. This paper has briefly discussed key findings of 'Lessons of Experience, India' (LOEI) study, which offers insights on how leaders in India learn to lead. The author in this paper has proffered a few suggestions to organisations that might help organisations to effectively deal with the challenges an organisation may encounter, while leveraging on the job assignments for leadership development. He has also proposed a few pointers for creating a learning ecosystem that synergistically blends both education and training-based formal and experience-centric informal approaches to groom effective organisational leaders.